Zebrafish class 1 phosphatidylinositol transfer proteins: PITPß and double cone cell outer segment integrity in retina - Ile, K.; Kassen, S.; Cao, C.; Vihtehlic, T.; Shah, S.; Mousley, Carl; Alb, J.; Huijbregts, R.; Stearns, G.; Brockerhoff, S.; Hyde, D.; Bankaitis, V. (2010)
Phosphatidylinositol transfer proteins (PITPs) in yeast co-ordinate lipid metabolism with the activities of specific membrane trafficking pathways. The structurally unrelated metazoan PITPs (mPITPs), on the other hand, are an under-investigated class of proteins. It remains unclear what biological activities mPITPs discharge, and the mechanisms by which these proteins function are also not understood. The soluble class 1 mPITPs include the PITPa and PITPß isoforms. Of these, the ß-isoforms are particularly poorly characterized. Herein, we report the use of zebrafish as a model vertebrate for the study of class 1 mPITP biological function. Zebrafish express PITPa and PITPß-isoforms (Pitpna and Pitpnb, respectively) and a novel PITPß-like isoform (Pitpng). Pitpnb expression is particularly robust in double cone cells of the zebrafish retina. Morpholino-mediated protein knockdown experiments demonstrate Pitpnb activity is primarily required for biogenesis/maintenance of the double cone photoreceptor cell outer segments in the developing retina. By contrast, Pitpna activity is essential for successful navigation of early developmental programs. This study reports the initial description of the zebrafish class 1 mPITP family, and the first analysis of PITPß function in a vertebrate. © 2010 John Wiley and Sons A/S.